Integrating Tajdid and Khaira Ummah in Islamic Character Education at Muhammadiyah Boarding School - Ikhwan, Afiful (LETIGES, 2025)
During the growing challenge of moral degradation and identity crisis in education, character development rooted in Islamic values is essential. This study aims to analyze the effectiveness of Islamic character education at Muhammadiyah Boarding School (MBS) through the implementation of Tajdid (renewal) and Khaira Ummah (the best people) values in shaping the Pancasila Student Profile. Using a library research method with a qualitative approach, the study examines scientific literature, policy documents, and research findings related to character education, Muhammadiyah ideology, and national character standards. The findings reveal that MBS applies an integrative and contextual educational model, combining classroom learning with 24-hour character coaching, value habituation, role modeling, and Islamic-based community life. Tajdid values support innovation, adaptability, and critical thinking, while Khaira Ummah promotes moral integrity, social responsibility, and civic engagement. These values are implemented through structured programs, such as the ISMUBA curriculum, reward–punishment systems, and collaborative teacher–dormitory mentoring. The study concludes that integrating Tajdid and Khaira Ummah values with the six dimensions of the Pancasila Student Profile creates a harmonious synergy between Islamic identity and national character. Limitations of the study include its conceptual nature without empirical field data. Future research should apply qualitative or mixed methods in specific MBS contexts to validate the model. This study offers originality by proposing a conceptual model of Islamic character education that bridges religious values and national ideals, contributing to Islamic education theory and national education policy discourse.